ENVIRONMENTAL REVIEW INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) KOMUNAL DI INDONESIA: STUDI KASUS IPAL KOMUNAL DI KABUPATEN SLEMAN YOGYAKARTA - marendra, fajar; Saputri, Dwi; Prasetya, Agus; Yuliansyah, Ahmad Tawfiequrrahman (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2024)
he communal domestic wastewater treatment plant (WWTP) in Distrik of Sleman, Yogyakarta built in 2006 and the latest in 2018. In this study, the assessment of six environmental aspects, quality of effluent, geographic location, land topography, receiving water bodies, floods hazard, and soil types, was carried out in the communal WWTP in the District of Sleman, Yogyakarta. Data collection techniques using Stratified Random Sampling combine with interview technic and field surveys, then an assessment is carried out based on the Likert scale. The results showed that the quality of effluent aspect gets an average score of 2.57, soil types (2.60), geographic location (2.83), land topography (3.13), receiving water bodies (3.17), and floods hazard (3.63). The quality of effluent aspect can improve by integrated with fixed bed process or electrochemical process. Overall, the environmental category of WWTP in the District of Sleman, Yogyakarta, gets an average score of 2.99 from the maximum value of 4 (quite a good).